Avaliação de assimetria nas arcadas dentárias de indivíduos com oclusão normal e má oclusão de Classe II - Scanavini, Paulo Estevão (2005)
The objective of this study was to evaluate the dental arch asymmetry s degree in individuals with normal occlusion and Class II malocclusion and to investigate the sexual dimorphism presence s in these individuals. 180 pars of study models were measured with a new appliance designed for analysis of dental arch asymmetries. These models were divided in three groups: Group 1: individuals with normal occlusion; Group 2: individuals with malocclusion Class II division 1; and Group 3: individuals with malocclusion Class II division 2. These individuals had age between 12 to 21 years old. Verified that everybody had dental arch asymmetry; the Group 1 had the smallest dental arch asymmetry s degree; the groups 2 and 3 had similar dental arch asymmetry s degree; the mandibular dental arches had a bigger dental arch asymmetry s degree than the maxillary dental arches; the midline had a opposite direction of the side of molars that had a mesial position, except for the maxillary dental arch in the Group 2 (Class II division 1); and, clinically, there wasn t sexual dimorphism for the dental arch asymmetry s evaluation.